2021
DOI: 10.1016/j.ijrobp.2021.07.288
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Radiotherapy Protocol Adherence on the Treatment Outcome in Patients With Locally Advanced NSCLC Treated With Concurrent Chemoradiation: Results From the Radiotherapy Quality Assurance of the International Randomized PET-Plan Trial

Abstract: Purpose/Objective(s): Cardiac radiation exposure is associated with an increased rate of adverse cardiac events in patients receiving radiation therapy for locally advanced non-small cell lung carcinoma (NSCLC). Previous analysis of practice patterns within the statewide Michigan Radiation Oncology Quality Consortium (MROQC) revealed 1 in 4 patients received a mean heart dose > 20 Gy and significant heterogeneity existed among treatment centers in using cardiac dose constraints. The purpose of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…CHART, GFPC-IFCT 02.01, PET-Plan, and PROCLAIM have formally reported radiotherapy QA [6] , [7] , [8] , [9] . The QA parameters differ between these clinical trials and are reported as isolated components.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CHART, GFPC-IFCT 02.01, PET-Plan, and PROCLAIM have formally reported radiotherapy QA [6] , [7] , [8] , [9] . The QA parameters differ between these clinical trials and are reported as isolated components.…”
Section: Discussionmentioning
confidence: 99%
“…This study reporting radiotherapy QA for the international randomised controlled CONVERT trial reports radiotherapy QA parameters and relates the dosimetric impact of contour variation, with treatment delivery compliance against patient outcome [6] , [7] , [10] , [12] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations